Butiiti artifact narratives inspiring ceramic forms - Balaba, Edward (Kampala, 2013)
Un-published dissertation (M.A. Fine Art) - Makerere University, 201 3
Includes bibliographical references
Keywords: Art, African; Decorative arts -- Uganda